Peran Negara Dalam Melindungi Hak Asasi Manusia di Indonesia Dalam Perspektif Hukum Islam - abdul halim; alya rahma; nazwha azzahra; zuryani, Nurul Aini; saprijal harahap, della harahap (Tabayyun : Journal Of Islamic Studies, 2023)
Human rights are rights inherent in a person that no one can contest. Therefore, the state's role in protecting these rights is also responsible for creating prosperity in social life. The problem formulation in this research is the role of the state in protecting human rights in Indonesia from an Islamic legal perspective. This research uses qualitative research methods with a descriptive approach. The findings in this research are the role of the state in protecting human rights Humans in Indonesia have been given such attention as can be seen from the many laws and regulations regarding Human Rights whose aim is to protect the rights of humans themselves. Islam also views the obligations of the state in carrying out its role as protector of human rights for all its people, must be maximal and every right must be fulfilled, because these rights absolutely come from Allah SWT and no one can interfere with them. However, in practice discrimination against human rights is still often encountered because injustice originating from the ruler himself.